A complete catalogue of broad-line AGNs and double-peaked emission lines from MaNGA integral-field spectroscopy of 10K galaxies: stellar population of AGNs, supermassive black holes, and dual AGNs - Fu, Y; Cappellari, M; Mao, S; Lu, S; Zhu, K; Li, R (Oxford University Press, 2023)
We analyse the integral field spectroscopy data for the ≈10 000 galaxies in final data release of the MaNGA survey. We identify 188 galaxies for which the emission lines cannot be described by single Gaussian components. These galaxies can be classified into (1) 38 galaxies with broad HαH and [O III] λ5007 lines, (2) 101 galaxies with broad HαH lines but no broad [O III] λ5007 lines, and (3) 49 galaxies with double-peaked narrow emission lines. Most of the broad-line galaxies are classified as active galactic nuclei (AGNs) from their line ratios. The catalogue helps us further understand the AGN-galaxy coevolution through the stellar population of broad-line region host galaxies and the relation between broad lines’ properties and the host galaxies’ dynamical properties. The stellar population properties (including mass, age, and metallicity) of broad-line host galaxies suggest there is no significant difference between narrow-line Seyfert-2 galaxies and Type-1 AGNs with broad HαH lines. We use the broad-HαH line width and luminosity to estimate masses of black hole in these galaxies, and test the MBH–σe relation in Type-1 AGN host galaxies. Furthermore, we find three dual AGN candidates supported by radio images from the VLA FIRST survey. This sample may be useful for further studies on AGN activities and feedback processes.